Missionary influence on African literary tendencies - Viriri, Advice (2016)
The advent of colonialism had far reaching implications in Africa. Western cultural imperialism was, and still is, implemented, inter alia, by the church and its missionary acolytes. Missionaries instilled Eurocentric value systems that were deemed vital for the successful execution of colonization. This paper will show that the literary tradition that emerged in Africa was not only intimately linked to Christianity, mission-controlled schools and the presses, but has been circumscribed by the socio-economic and political realities of colonialism. As shall be seen, Africans did not regard Christianity as part of the colonization agenda. Missionaries linked Christian mystical life with literacy hence this investigation examines whether the mythicized African fiction is devoid of any realism at all.